PENERAPAN MODEL PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MTS NEGERI 1 PONTIANAK - Gustini, Gustini; Buwono, Sri; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine students' critical thinking skills toward IPS subject inVIII F Grade of MTS Negeri 1 Pontianak with the application of problem posing learning model. The variables in this study were problem posing learning model and students' critical thinking skills using Quasi Experimental Design research method. The data samples of this research were from 30 students of VIII F Grade in MTs Negeri 1 Pontianak. The data collection used direct observation techniques, documentary study techniques, and measurement techniques. The results showed of the comparison score between the first posttest with the second posttest showed that 20 out of 30 students experienced an increase and the comparison of the second posttest with the third posttest indicated that 17 out of 30 students had increased. Therefore, generally the application of the problem posing learning model was proven could improve students' critical thinking skills in VIII F Grade of MTS Negeri 1 Pontianak. Keyword: IPS, Problem Posing, Student’ Critical Thinking